Sosialisasi Penggunaan Aplikasi Quizizz untuk Mata Kuliah Pengantar Teknologi Informasi pada Mahasiswa Semester 1 UNIPMA - Sekreningsih Nita; Kelik Sussolaikah; Jonathan Alfa G.J; Firza Muhammad Ilham (Jurnal Informasi Pengabdian Masyarakat, 2025)
This socialization activity is packaged in the form of training and mentoring which aims to increase understanding in utilizing digital platforms and technology regarding the Quizzizz application as an alternative learning model for the Introduction to Information Technology (PTI) course for UNIPMA semester 1 students. Based on the results of observations, the author found problems faced by class 1E students who took PTI courses, namely the lack of enthusiasm and activeness of students in attending lectures in class. Therefore, the author is interested in carrying out learning outreach activities using the Quizizz application. Quizizz is a web tool for creating interactive quizzes that can be used in classroom learning and outside of class as homework, so that students can run them at any time. The method of implementing socialization is by means of presentations, lectures, discussions and training and mentoring. The objectives of this service include 1) Students will be more responsive, interesting and fun; 2) Providing innovation in learning evaluation models; 3) Students are able to understand PTI material more deeply; 4) Student learning outcomes increase. The final results showed that 90% of the 21 students stated that by using the Quizizz application as an interesting, fun and responsive digital platform because it is in the form of an interactive quiz game for online learning, it can provide deeper understanding and is easy to understand for students, especially those taking PTI courses.